MTHFR 677C-->T polymorphism and risk of coronary heart disease: a meta-analysis. - Klerk, M; Verhoef, P; Clarke, R; Blom, H; Kok, F; Schouten, E (2002)
CONTEXT: In observational studies, individuals with elevated levels of plasma homocysteine tend to have moderately increased risk of coronary heart disease (CHD). The MTHFR 677C-->T polymorphism is a genetic alteration in an enzyme involved in folate metabolism that causes elevated homocysteine concentrations, but its relevance to risk of CHD is uncertain. OBJECTIVE: To assess the relation of MTHFR 677C-->T polymorphism and risk of CHD by conducting a meta-analysis of individual participant data from all case-control observational studies with data on this polymorphism and risk of CHD. DATA SOURCES: Studies were identified by searches of the electronic literature (MEDLINE and Current Contents) for relevant reports published before June 2001 (using the search terms MTHFR and coronary heart disease), hand searches of reference lists of original studies and review articles (including meta-analyses) on this topic, and contact with investigators in the field. STUDY SELECTION: Studies were included if they had data on the MTHFR 677C-->T genotype and a case-control design (retrospective or nested case-control) and involved CHD as an end point. Data were obtained from 40 (34 published and 6 unpublished) observational studies involving a total of 11 162 cases and 12 758 controls. DATA EXTRACTION: Data were collected on MTHFR 677C-->T genotype, case-control status, and plasma levels of homocysteine, folate, and other cardiovascular risk factors. Data were checked for consistency with the published article or with information provided by the investigators and converted into a standard format for incorporation into a central database. Combined odds ratios (ORs) for the association between the MTHFR 677C-->T polymorphism and CHD were assessed by logistic regression. DATA SYNTHESIS: Individuals with the MTHFR 677 TT genotype had a 16% (OR, 1.16; 95% confidence interval [CI], 1.05-1.28) higher odds of CHD compared with individuals with the CC genotype. There was significant heterogeneity between the results obtained in European populations (OR, 1.14; 95% CI, 1.01-1.28) compared with North American populations (OR, 0.87; 95% CI, 0.73-1.05), which might largely be explained by interaction between the MTHFR 677C-->T polymorphism and folate status. CONCLUSIONS: Individuals with the MTHFR 677 TT genotype had a significantly higher risk of CHD, particularly in the setting of low folate status. These results support the hypothesis that impaired folate metabolism, resulting in high homocysteine levels, is causally related to increased risk of CHD.